Effectiveness of a mobile phone application to increase access to sexual and reproductive health information, goods, and services among university students in Uganda: a randomized controlled trial - Elly Nuwamanya; Robinah Nalwanga; Afra Nuwasiima; Janet U. Babigumira; Francis T. Asiimwe; Joseph B. Babigumira; Vitalis P. Ngambouk (BMC, 2020)
Abstract Background University students are one of the most vulnerable groups to sexual reproductive health [SRH] threats like sexually transmitted infections [STIs], unwanted pregnancies, and unsafe abortions and often have limited access to SRH information, goods, and services. This study assessed the effectiveness of using a mobile phone application (APP) to increase access to SRH information, goods, and services among university students in Uganda. Methods Using data from a double-blinded randomized controlled trial, participants were randomly assigned to both the intervention (APP) and control (standard of care) arms. We executed descriptive analyses for baseline demographic characteristics by intervention, difference in difference (DID), and quantile regression analyses for both primary and secondary outcomes. Results The median age of participants was 21 years of age, and the majority were female (over 60%), unemployed (over 85%) and Christian (90%). Over 50% were resident in off-campus hostels and in a relationship. Between baseline and end-line, there was a significant increase in SRH knowledge score (DID = 2, P < 0.001), contraceptive use (DID = 6.6%, P < 0.001), HIV Voluntary testing and counselling (DID = 17.2%, P < 0.001), STI diagnosis and treatment (DID = 12.9%, P < 0.001), and condom use at last sex (DID = 4%,P = 0.02) among students who used the APP. There was a significant 0.98 unit increase in knowledge score (adjusted coefficient = 0.98, P < 0.001), a significant 1.6-fold increase in odds of contraceptive use (adjusted coefficient = 1.6, P = 0.04), a significant 3.5-fold increase in HIV VCT (adjusted coefficient = 3.5, P < 0.001), and a significant 2-fold increase in odds of STI testing and treatment (adjusted coefficient = 1.9, P < 0.001) after adjusting for demographic characteristics among APP users compared to the control group. Conclusion A mobile phone application increased sexual and reproductive health information (knowledge score), access to goods (contraceptives), and services (HIV voluntary testing and counseling and sexually transmitted infection diagnosis and management) among sexually active university students in Uganda. Further technical development, including the refinement of youth-friendly attributes, extending access to the app with other platforms besides android which was pilot tested, as well as further research into potential economic impact and paths to sustainability, is needed before the app is deployed to the general youth population in Uganda and other low-income settings. Trial registration MUREC1/7 No. 07/05-18. Registered on June 29, 2018.